KOHESIVITAS KELOMPOK SEBAGAI PEMODERASI PENGARUH PARTISIPASI PENGANGGARAN TERHADAP SENJANGAN ANGGARAN - Putri, Aprilita Catur; Ratna Sari, Maria M. (E-Jurnal Akuntansi, 2016)
Management participation in the budgeting process tends to create budgetary slack depending on the interests held by management. The purpose of this study is to determine the effect of budgetary participation on the budgetary slack and to recognize group cohesiveness as a moderating influence on budgetary participation to the budgetary slack. This study was conducted in 52 BPR in Badung. This research used primary data obtained directly by distributing questionnaires to 145 respondents using purposive sampling technique. The resulted data were carried out on statistically analysis using Moderated Regression Analysis (MRA). Results from this study stated that the budgetary participation positive influence on budgetary slack. Group cohesiveness can be moderate (weaken) the effect of budgetary participation on budgetary slack. Advice can be given to the BPR that oversee the management participation in the preparation and increase the cohesiveness of the group within the organization. In addition, it can add other variables such as personal character and  the adequacy targets for further research.
Keywords: budgetary participation, group cohesiveness, budgetary slack